Islāḥ and Restorative Justice in the Resolution of Domestic Violence Cases: A Normative Analysis of Victim Protection - Vivi Purnamawati; Lina Rosmalina Aslami (Universitas Islam Negeri Raden Intan Lampung, 2025)
Domestic violence is frequently addressed through reconciliation mechanisms, including restorative justice and the concept of iṣlāḥ, due to its occurrence within ongoing personal relationships. However, such approaches raise significant normative concerns, as they may undermine victim protection and perpetuate asymmetric power relations. This study aims to conduct a normative analysis of the integration of iṣlāḥ and restorative justice in the resolution of domestic violence cases, with particular emphasis on safeguarding victims’ rights. Employing a normative legal research method with conceptual and statutory approaches, this study examines Law No. 23 of 2004 on the Elimination of Domestic Violence, Supreme Court Regulations on restorative justice, and Islamic legal literature on iṣlāḥ. The analysis is framed by restorative justice theory, the concepts of maṣlaḥah and maqāṣid al-sharīʿah, as well as theories of the objectives of law. The findings indicate that although iṣlāḥ and restorative justice share a convergent orientation toward recovery, their application in domestic violence cases can only be justified when grounded in the principles of victim protection, genuinely voluntary consent free from coercion, and adequate institutional oversight as prerequisites for the legitimacy of reconciliation.